A New Metal-Free Carbon Hybrid for Enhanced Photocatalysis - Sun, Hongqi; Zhou, Guanliang; Wang, Yuxian; Suvorova, A.; Wang, Shaobin (American Chemical Society, 2014)
Carbon nitride (C3N4) is a layered, stable, and polymeric metal-free material that has been discovered as a visible-light-response photocatalyst. Owing to C3N4 having a higher conduction band position, most previous studies have been focused on its reduction capability for solar fuel production, such as hydrogen generation from water splitting or hydrocarbon production from CO2.However, photooxidation ability of g-C3N4 is weak and has been less explored, especially for decomposition of chemically stable phenolics. Carbon spheres prepared by a hydrothermal carbonization of glucose have been widely applied as a support material or template due to their interesting physicochemical properties and the functional groups on the reactive surface. This study demonstrated that growth of carbon nanospheres onto g-C3N4 (CN-CS) can significantly increase the photooxidation ability (to about 4.79 times higher than that of pristine g-C3N4) in phenol degradation under artificial sunlight irradiations. The crystal structure, optical property, morphology, surface groups, recombination rate of electron/hole pairs, and thermal stability of CN-CS were investigated by a variety of characterization techniques. This study contributes to the further promising applications of carbon nitride in metal-free catalysis.